Terjebak Ketegangan Budaya: Pemuda di Tengah Tatanan Sosial Baru Pandemi: ADAPTASI PEMUDA TERHADAP TATANAN SOSIAL PANDEMI - B.J. Sujibto; Aulia Rachma Diah (LIPI Press, 2022)
Abstract This article discusses how youths adapt and challenge the social orders introduced by the COVID-19 protocol and other socio-cultural consequences. While maximizing social role and social status in society through durable processes, youths’ interpretation of the pandemic rules have created important discourses in the context of shaping new pandemic cultures. Having acknowledged as digital natives on the one hand, and agents of change on the other hand, youths have their own way of adapting and challenging the new cultures of a pandemic. By using a qualitative approach, primary data were collected through interviews with undergraduate students in Yogyakarta, and then supported by secondary data collected through observations, documents and news. This article has found three important points. The first is an awareness of maintaining oneself health and its family which then leads to a collective spirit, that is to build a healthy community. The second is an accelerative way to the digital world giving youth a flash opportunity to take part in the social sphere. The pandemic has been accelerating the digital platforms and at the same time has forced youths to be able to use it. The third is cultural tensions inevitably arising due to the constant process of adaptation to the pandemic rules. These three findings are staged in a social process to see the role of actors and the social structures in particular. Keywords: COVID-19, pandemic culture, cultural tension, youth, social process